Literacy practices for the K’anjob’al language revitalization from Chiapas, Mexico - Córdova-Hernández, Lorena (2022)
This paper describes the first documentation exercise for revitalizing the K’anjob’al language through the production of bilingual material (indigenous language-Spanish) in a community of high linguistic vitality in the municipality of La Trinitaria Chiapas (Mexico). The production of this material promoted literacy practices, understood as social practices in which reading and writing are used for specific objectives and purposes, in a context where such practices are limited or non-existent. Based on collaborative anthropology, the methodology consisted of eliciting information from three field seasons in the last semester of 2019. The results obtained from two phases are presented in the development section: i) documentation of language and culture and ii) material validation. Therefore, the progress of this research is based on three premises: a) through literacy practices to strengthen identity processes among the speakers of this language in Mexico; b) to produce texts for real contexts and users, that is, materials for family and intercommunity consumption; c) through the promotion of biliteracy, to document cultural memory and make the use of written language visible to generate future revitalizing initiatives at a regional level.